Influence of processing conditions on the β-Phase content of PVDF samples produced by tape extrusion - Martins, R. S. (2012)
This research team has been working during the last couple of years on the development of industrial scalable technologies, based on the extrusion processing technique, for the prodution of piezoeletric products. This specific work comprises a study on the effect of tape extrusion processing conditions on the content of PVDF β-phase. For this purpose the extruded samples were uniaxially stretched up to ratios of 6, at 80ºC and 120ºC, being the β-phase content analysed by FTIR. Subsequently, the samples were corona poled and their piezoelectric coefficient d33 was measured. The results obtained allowed to conclude that the extrusion processing variables, with the exception of the stretching temperature and ratio, do not have a strong influence on the β-phase content and piezoelectric response of PVDF.